Striatal Gαolf/cAMP Signal-Dependent Mechanism to Generate Levodopa-Induced Dyskinesia in Parkinson’s Disease - Goto, Satoshi (Frontiers in Cellular Neuroscience, 2017)
The motor symptoms of Parkinson’s disease result from striatal dopamine deficiency due to a progressive degeneration of nigral dopaminergic cells. Although dopamine replacement therapy is the mainstay to treat parkinsonian symptoms, a long-term daily administration of levodopa often develops levodopa-induced dyskinesia (LID). LID is closely linked to the dysregulation of cyclic adenosine monophosphate (cAMP) signaling cascades in the medium spiny neurons (MSNs), the principal neurons of the striatum, which are roughly halved with striatonigral MSNs by striatopallidal MSNs. The olfactory type G-protein alpha subunit (Galphaolf) represents an important regulator of the cAMP signal activities in the striatum, where it positively couples with D1-type dopamine receptor (D1R) and adenosine A2A receptor (A2AR) to increase cAMP production in the MSNs. Notably, D1Rs are primarily expressed in striatonigral MSNs, whereas D2Rs and A2ARs are expressed in striatopallidal MSNs. Based on the evidence obtained from parkinsonian mice, we hypothesized that in the dopamine-denervated striatum with D1R hypersensitivity, a repeated and pulsatile exposure to levodopa might cause a usage-induced degradation of Galphaolf proteins in striatal MSNs, resulting in increased and decreased levels of Galphaolf protein in the striatonigral and striatopallidal MSNs, respectively. As a principal cause for generating LID, this might lead to an increased responsiveness to levodopa exposure in both striatonigral and striatopallidal MSNs. Our hypothesis reinforces the long-standing concept that LID might result from the reduced activity of the striatopallidal pathway and has important clinical implications.